Iron deficiency anemia in obstetrics - T.P. Zefirova; E.Yu. Yupatov; R.R. Mukhametova (LCC «Medicine-Inform», 2021)
T.P. Zefirova1, E.Yu. Yupatov1, R.R. Mukhametova2 1Kazan State Medical Academy - Branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 2Kazan Federal University, Kazan, Russian Federation This paper discusses the anemia of pregnancy that is a global issue affecting tens of millions of women. The prevalence of anemia increases as pregnancy progresses and is maximum in the third trimester having a negative impact on pregnancy course. Major causes of unfavorable perinatal outcomes related to anemia are addressed. The authors highlight that anemia of pregnancy increases the rate of stillbirths, premature birth, and intrauterine growth restriction. The mechanisms accounting for placental insufficiency (e.g., circulatory hypoxia, abnormal blood rheology, microcirculatory abnormalities) are described. Current data on the increased risk of maternal death in anemia are discussed. Its major causes are hemorrhages, infectious septic complications, and thromboses. Diagnostic and therapeutic modalities for anemia are emphasized. Personalized management strategy and rational choice of iron products require an understanding of iron metabolism and the knowing of the role of hepcidin-mediated inhibition of the mechanism of iron metabolism. Keywords: iron deficiency anemia, pregnancy, maternal mortality, placental insufficiency, hep-cidin, pre-pregnancy preparation, hemodilution. For citation: Zefirova T.P., Yupatov E.Yu., Mukhametova R.R. Iron deficiency anemia in obstetrics. Russian Journal of Woman and Child Health. 2021;4(1):53-58. DOI: 10.32364/2618-8430-2021-4-1-53-58.